2023
DOI: 10.1111/acel.13935
|View full text |Cite
|
Sign up to set email alerts
|

Circadian regulation in aging: Implications for spaceflight and life on earth

Abstract: Alterations in the circadian system are characteristic of aging on Earth. With the decline in physiological processes due to aging, several health concerns including vision loss, cardiovascular disorders, cognitive impairments, and muscle mass loss arise in elderly populations. Similar health risks are reported as “red flag” risks among astronauts during and after a long‐term Space exploration journey. However, little is known about the common molecular alterations underlying terrestrial aging and space‐relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 262 publications
0
2
0
Order By: Relevance
“…Among the many physiological alterations occurring during aging, the exhaustion of the adult stem cell reservoir and dysregulation of circadian rhythms are emerging [132][133][134]. Prospectively, deepening the currently appearing complex interplay between the cellular biology of stem cells and rhythmic time-keeping mechanisms may offer new opportunities for healthy and longer life.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many physiological alterations occurring during aging, the exhaustion of the adult stem cell reservoir and dysregulation of circadian rhythms are emerging [132][133][134]. Prospectively, deepening the currently appearing complex interplay between the cellular biology of stem cells and rhythmic time-keeping mechanisms may offer new opportunities for healthy and longer life.…”
Section: Discussionmentioning
confidence: 99%
“…Females tend to exhibit an earlier circadian peak phase as compared to males, and previous reports showed a different therapeutic impact among females and males in colorectal cancer patients treated under chrono-modulated therapy regimes [17,18]. Aging may also influence the CR resulting in dampening of the circadian amplitude, an advance of circadian phase, or result in gain or loss of rhythmic circadian expression [19][20][21][22][23][24]. Recent transcriptomics studies further revealed differential regulation of circadian gene expression between middle/older aged individuals, and younger adults [23,25].…”
Section: Introductionmentioning
confidence: 99%